Social Media’s Position in Web Within the Scope of Online Information Flow - Polat, Burak (European Journal of Social Science Education and Research, 2017)
World Wide Web (Web) is commercialized at the very end of 20th century and now, in the 21st century, almost half of the human society is using it. Web technologies have evolved and a relatively small set of them has a capacity of simulating complexity of sociality via interpersonal interactions; to define this small set many terms have been suggested, yet social media has been widely used by many scholars. Social media is a set of online communication networks that constitutes a crucial hub for producing, accessing and diffusing information. Inquiry on understanding the online flow of the information, it is essential to understand the topological position of social media within web’s mesh structure. In this paper at first communication and information terms will be defined and social media will be discussed within the scope of complexity and information flow terms from network science and communication science perspective. At last, a graph analysis example on social media’s topological position within web will be shared to emphasize social media’s importance on online information flow.
Keywords: Social Media, Convergence Model of Communication, Information Flow, Communication Theory, Network Theory